2021
DOI: 10.1007/s11356-021-14934-y
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19-related knowledge, risk perception, information seeking, and adherence to preventive behaviors among undergraduate students, southern Iran

Abstract: Globally, the novel COVID-19 has been recognized as one of the most important pandemics and devastating diseases in human history, with many deaths and morbidities. In the absence of effective treatment and limited supply of COVID-19 vaccine, people must adhere to recommended preventive measures. This study aimed to determine the level of COVID-19 knowledge, perceived susceptibility, perceived severity, and health information-seeking and preventive behaviors as well as associated factors with preventive behavi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
36
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(48 citation statements)
references
References 46 publications
8
36
0
1
Order By: Relevance
“…Further, we test the Granger causality among the three variables in the NN group, and we find that the new reported COVID-19 cases are the Granger causes of vaccination and mobility (see Figure 4 ). The propelling effect of the pandemic on vaccine inoculations can be attributed to increased risk perceptions and self-preservation behaviors, which agrees with the outcomes of the existing surveys on the perception of the pandemic and vaccine intensions [ 40 , 41 , 42 ]. The Granger causal relation between COVID-19 cases and mobility might be explained by increased vaccine inoculations; with reported cases increased, people are rushing to vaccination sites to get inoculated.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Further, we test the Granger causality among the three variables in the NN group, and we find that the new reported COVID-19 cases are the Granger causes of vaccination and mobility (see Figure 4 ). The propelling effect of the pandemic on vaccine inoculations can be attributed to increased risk perceptions and self-preservation behaviors, which agrees with the outcomes of the existing surveys on the perception of the pandemic and vaccine intensions [ 40 , 41 , 42 ]. The Granger causal relation between COVID-19 cases and mobility might be explained by increased vaccine inoculations; with reported cases increased, people are rushing to vaccination sites to get inoculated.…”
Section: Resultssupporting
confidence: 86%
“…Furthermore, we show that the reported COVID-19 cases are Granger causal causes of vaccine inoculations in the NN group. Our observation explains the rationality of the negative vaccination–mobility and mobility–cases relations, as the perceived risk of this pandemic is a major driver of self-protective behaviors and vaccine acceptance [ 40 , 41 , 42 , 44 ].…”
Section: Discussionmentioning
confidence: 83%
“…Factors affecting individuals' health behaviours such as perceived seriousness and susceptibility to COVID‐19, perceived barriers, perceived benefits, motivating factors and self‐efficacy regarding compliance with COVID‐19 preventive behaviours may also have an effect. In a study conducted of university students in Iran, it was reported that the level of COVID‐19‐related knowledge was not associated with COVID‐19 preventive behaviours, whereas it was found to be associated with perceived susceptibility, perceived severity and health information seeking behaviours (Rayani et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Employees in the health sector have been the most affected frontline workers during the pandemic [ 54 ]. This has been largely attributed to their level of exposure, given the nature of their job [ 55 ] and risk of interacting with patients suffering from COVID-19 [ 56 ], as well as the risk of being infected by work colleagues [ 57 ]. It is, therefore, important to understand how the perceived risk of COVID-19 influences employee decision-making.…”
Section: Introductionmentioning
confidence: 99%